Sociocultural and epidemiological characterization of a focus of cutaneous leishmaniasis in cimitarra, santander (2000)
An epidemiological and sociocultural characterization regarding cutaneous leishmaniasis (CL) as well as an active case search were carried out in the village of Filo de Chontarales in the town of Cimitarra, department of Santander, with the aim of identifying social and environmental conditions contributing to the appearance and persistence of CL in this zone. Information was collected by interviewing 131 people and by field visits to the village. At the same time a sociocultural survey was applied, Montenegro skin test (MST) was performed on 203 people, and persons in whom CL was suspected were subjected to diagnostic confirmation and given treatment. The prevalence of a positive MST in the population was 92%, without any significant differences between sex and age groups. 64 cases of CL were detected, and all of them were treated with Glucantime with good clinical results. Entomological studies showed the presence of Lutzomyia longipalpis. CL is a health problem, which is recognized and considered as such by the community. This perception is expressed in the search for treatments when lesions appear and in the development and use of a variety of popular treatments. The population surveyed recognizes the disease as "pito bite" (100 %). However, only 3,8 % of the population properly recognizes the "pito", while Lutzomyia is identified by 100 % of the population, with the popular name of "zolamilla" and no disease is attributed to this insect. This fact might have important consequences regarding the prevention of CL in this zone. This is a high risk zone for CL and therefore it is necessary to create a preventive model which takes into account the conception, understood as the population's social representation of CL, particularly regarding its insect vector.